When depression envelops frontotemporal dementia: The differential diagnostic frame through a case report - U. Altunoz; J. Menstell; M. Ziegenbein (European Psychiatry, 2022)
Introduction Frontotemporal dementia (FTD) is common in presenile population. The overlapping symptoms with other psychiatric disorders can lead to wrong/late diagnosis which cause delays/difficulties regarding case-management. Especially, long-standing and/or late-onset depression can descriptively envelop bvFTD (behavioral-variant) and leads to unnecessary treatments and increased distress. It’s important to implement a descriptive diagnostic algorithm which will help clinicians to distinguish the phenomenology of these disorders.